Academic Dishonesty Differences Evaluated by Academic Identity Status in Undergraduate Students - Shalihat, Zulfa Qonita; Febriani, Arum (Universitas Ahmad Dahlan, 2025)
Academic dishonesty has become a pressing concern in higher education, as illustrated by 2024 data from the Indonesian Corruption Eradication Commission (Komisi Pemberantasan Korupsi, KPK) indicating that more than half of respondents admitted to engaging in cheating. Such behavior may be shaped by academic identity status, defined as an individual’s self-perception and commitment within the academic domain. However, empirical evidence on this association remains scarce, particularly among Indonesian undergraduate students. The present study examined differences in academic dishonesty across academic identity statuses in a sample of 216 Indonesian undergraduates aged 18–25 years. Using a quantitative design, participants completed the Academic Dishonesty Scale and the Academic Identity Measure (AIM). A one-way ANOVA revealed significant differences in academic dishonesty scores across identity statuses, F(3, 212) = 5.239, p = .002, η² = .069. Post hoc comparisons indicated that students with a moratorium identity status reported higher levels of academic dishonesty than those with an achievement identity status, whereas no other pairwise differences reached statistical significance. These findings extend the literature on academic dishonesty by integrating identity status theory within the Indonesian higher education context and suggest that academic identity development should be considered when designing targeted preventive and remedial interventions in universities.